Кореляція людського та штучного інтелекту :виклики та перспективи - Долгий, А. І. (Національний технічний університет "Харківський політехнічний інститут", 2021)
У тезах розглянуто проблему співвідношення людського та штучного інтелекту. Проаналізовано цивілізаційні виклики технологічної доби кіберсуспільства. Визначено екзистенційні загрози технологічного простору та ШІ. Встановлено шляхи вирішення означених викликів. Показано цивілізаційні перспективи співвідношення людського інтелекту та ШІ.

The thesis considers the problem of the ratio of human and artificial intelligence. The civilization challenges of the technological age of cyber society are analyzed. Existential threats of technological space and AI have been identified. Ways to solve these challenges have been identified. The civilization perspectives of the ratio of human intelligence and AI are shown.
Correlation of human and artificial intelligence: challenges and possibilities
Keywords: людський інтелект; штучний інтелект; хомодеус; кіберсуспільство; трансценденція; раціональне; ірраціональне; human intelligence; artificial intelligence; homodeus; cyber society; transcendence; rational; irrational